Tonnoma's Story : Women's Work and Empowerment in Burkina Faso - Grun, Rebekka; Jillson, Irene; Kantiono, Florence; Kedote, GIlberte; Ouangraoua, Nathalie; Daouda-Koudjo, Moudjibath (Washington, DC: World Bank, 2020)
Tonnoma is the protagonist of her own story of development. 26 years old, illiterate, and married to a man 15 years her senior, Tonnoma lives in a rural area of Burkina Faso. Before finding employment with the Youth Employment and Skills Development Project, she performed household chores and depended on her husband’s irregular income to meet the family’s needs. His income was not always sufficient, and they lost their fourth child to poverty. Tonnoma’s Story: Women’s Work and Empowerment in Burkina Faso is based on actual events and the experiences of numerous women. It draws directly from the results of qualitative research on the factors impeding or promoting women’s ability to work in Burkina Faso. It offers readers a glimpse into the daily lives of women who live in a rural environment and want to work. This book shows us that emotional relationships matter, that the social and cultural landscape we are born into matters, and that if we want to conduct effective development, we have to listen carefully to the beneficiaries. How do they perceive their circumstances? What influences their behaviors? What helps or hinders women’s access to employment—in their view? This book encourages readers to reflect on how to conduct more beneficiary-centered and participatory international development that better responds to realities on the ground.